Cognitions and coping strategies of elite skiers: an exploratory study of young developing athletes - Rotella, R. J.; Gansneder, B.; Ojala, D.; Billing, J. (Journal of Sport Psychology, 1980)
Highly competitive adolescent skiers were evaluated for precompetition thought content. The better skiers focused on the difficult parts of the race course and then planned strategies for preparing for the race. Thinking positively without including task-specific preparatory concentration is not enough to produce the best performance but may be better than worry. The visual content of the imagination of the better skiers was the anticipated visual input of the performance. The course was seen as it would be encountered, that is, the athletes imagined looking through their eyes at the course just as it would occur in a race. Poorer performers saw themselves skiing the course from an external perspective. Implication: Prior to competing, planning what one does and anticipating what will be experienced is a feature of preparations of better performing skiers. The focus of the planning should be from an internal rather than external perspective.